O nekaterih vprašanjih v zvezi z dopuščeno revizijo po ZPP-D - Dolenc, Mile (Pravni letopis, 2009)
The new regime of revision, which is dominated by the introduction of permitted revision, is certainly more far reaching than it might appear at first sight. It will relieve part of the Supreme Court, acting in civil proceedings, of its excessive workload and allow it to deal in sufficient depth with the essential issues of court practice. The Supreme Court will in this way (by selecting cases) assume extreme responsibility for the very functioning of the entire judicial system and the rule of law in general. A refined feeling will be needed in searching for the right balance of the interests of the parties in each of the revision cases and interests of the whole legal system. At the beginning many practical problems, which have already emerged or are yet to be perceived when the new system of permitted revision will be in full use, will have to be resolved. To be successful in the eyes of the public and the parties to the proceedings the Supreme Court, as the highest court in the country, will probably have to thoroughly consider some alternative methods of working and its different internal organization.
Keywords: pravdni postopek; pritožba; revizija